Energy, transport and environment indicators. 2015 edition (Luxembourg, 2015)
"TThe multi-thematic statistical book Energy, transport and environment indicators comprises a broad set of data collected by Eurostat. It presents the EU’s main indicators for energy, transport and environment with particular focus on sustainable development and climate change. The publication provides data for the European Union and its Member States, while some indicators include also data for the EFTA countries and candidate and potential candidate countries to the EU. "